The Analysis of Figurative Language Used in the Lyric of Firework by Katy Perry (A Study of Semantic) - Hariyanto, Hariyanto (Universitas Islam Negeri Raden Intan Lampung, 2017)
Figurative language is a part of semantic. This research analyzed the figurative language used in the lyric of firework by Katy Perry. The aims of this research are to find out the figurative languages used in the lyric of firework and to analyze the contextual meaning of figurative language used in that song. It is expected the result of this study will be useful for the reader especially in knowing what figurative language is and what kinds of figurative language are. The design of this research is descriptive qualitative research. The data of song is got from kapanlagi.com entitle firework. The result found that there are some kinds of figurative language used in Katy perry’s song entitle firework, such as simile, metaphor, hyperbole, affiliation, symbolic, paradox, and personification. The contextual meaning of each figurative language is also stated clearly. The conclusion of this research is there are some kinds of figurative language use by Katy Perry in her song entitle firework.